2004
DOI: 10.1123/japa.12.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in Physical Activity Groups for Older Adults: A Qualitative Analysis

Abstract: The purpose of this study was to determine whether a theory-based framework could be used to deductively identify and understand the characteristics of motivational leaders of physical activity groups for older adults. Participants were 23 older adults (mean age = 78.5 ± 8.0 years, 65% women). An interviewguide approach was employed to elicit older adults' thoughts on important characteristics of physical activity group leaders. The data suggested that effective leaders are those whom the participants feel are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…For example, perceived psychological benefits of participants (Bostwick & Brown, 2004), the leadership of qualified exercise leaders, and the development of personal relationships (Estabrooks et al, 2004) are all factors associated with program adherence. In addition, exercising in a group environment were motivators for participation in persons with schizophrenia (Fogarty & Happell, 2005) and multiple sclerosis (Dodd, Taylor, Denisenko, & Prasad, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…For example, perceived psychological benefits of participants (Bostwick & Brown, 2004), the leadership of qualified exercise leaders, and the development of personal relationships (Estabrooks et al, 2004) are all factors associated with program adherence. In addition, exercising in a group environment were motivators for participation in persons with schizophrenia (Fogarty & Happell, 2005) and multiple sclerosis (Dodd, Taylor, Denisenko, & Prasad, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…However, few studies have systematically investigated exercise leader behaviors or the qualifications required to be an effective fitness leader. One recent study (12) examined the characteristics of motivational leaders of physical activity groups for older adults. Results showed that older adults responded best when leaders exhibited competency to lead exercise, treated the participants as individuals, and demonstrated the ability to foster social interaction between members in the class.…”
Section: Introductionmentioning
confidence: 99%
“…Estabrooks et al (2004) found that older adults want to have a physical activity program leader who is competent and qualified to lead the exercises. Furthermore, they proposed that exercise instructors for older adults need to demonstrate that they can set an appropriate exercise environment, including appropriate music and instructional voice, but also facilitate group integration in a way that a sense of cohesion and membership can develop.…”
Section: Discussionmentioning
confidence: 98%
“…Older adults not previously involved in a structured exercise class demonstrated increased exercise adherence when special effort was placed on team-building and bonding during the group exercise intervention (Estabrooks et al, 2004). The interventions using a combination of cognitivebehavioral or behavioral strategies, such as self-monitoring, goal setting, support, feedback, and relapse prevention, were effective (King, Rejeski, & Buchner, 1998).…”
Section: Group-based Exercise In Frail Older Adultsmentioning
confidence: 94%